2009
DOI: 10.1007/s00442-009-1432-8
|View full text |Cite
|
Sign up to set email alerts
|

No interaction between competition and herbivory in limiting introduced Cirsium vulgare rosette growth and reproduction

Abstract: Both competition and herbivory have been shown to reduce plant survival, growth, and reproduction. Much less is known about whether competition and herbivory interact in determining plant performance, especially for introduced, weedy plant species in the invaded habitat. We simultaneously evaluated both the main and interactive effects of plant neighbors and insect herbivory on rosette growth and seed reproduction in the year of flowering for Cirsium vulgare (bull thistle, spear thistle), an introduced Eurasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
(47 reference statements)
4
13
2
Order By: Relevance
“…These results are based on a simple, two-stage matrix model; population growth rate is not influenced by the number of stages included in a matrix model (Tenhumberg et al 2009;Salguero-Gómez and Plotkin 2010). These findings are consistent with experimental studies showing that insect herbivory often severely reduce the fecundity of thistles (Louda and Potvin 1995;Rose et al 2005Rose et al , 2011Suwa et al 2010). Similar to the native C. altissimum, the late flowering time of C. vulgare combined with the occurrence of late-season herbivores, such as Homoeosoma eremophasma (Pyralidae) (Takahashi 2006), likely prevent successful compensatory seed production (Rose et al 2011).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These results are based on a simple, two-stage matrix model; population growth rate is not influenced by the number of stages included in a matrix model (Tenhumberg et al 2009;Salguero-Gómez and Plotkin 2010). These findings are consistent with experimental studies showing that insect herbivory often severely reduce the fecundity of thistles (Louda and Potvin 1995;Rose et al 2005Rose et al , 2011Suwa et al 2010). Similar to the native C. altissimum, the late flowering time of C. vulgare combined with the occurrence of late-season herbivores, such as Homoeosoma eremophasma (Pyralidae) (Takahashi 2006), likely prevent successful compensatory seed production (Rose et al 2011).…”
Section: Discussionsupporting
confidence: 77%
“…Despite the clipping, however, the insecticide treatment increased heterospecific plant cover (ESM 4). Heterospecific competitors can reduce growth and seed production of C. vulgare (Suwa et al 2010;. Therefore, the increase in heterospecific cover associated with the insecticide treatment makes our estimate of the effect of herbivory on C. vulgare population growth a conservative one.…”
Section: Insecticide Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Photo credit: Masaru Takahashi. Suwa et al 2010). Their median estimate of predispersal seed predation (76.5%) combined with our 58% median reduction in seedling density indicates that herbivory can reduce lifetime fitness of C. vulgare by .90%.…”
Section: Role Of Propagule Pressurementioning
confidence: 72%
“…Further, in a parallel study, we found that any subsequent compensatory density-dependent processes did not alter predictions for population size and dynamics suggested by the herbivory effects on the seedling stage (J. O. Eckberg, B. Tenhumberg, and S. M. Louda, unpublished data). Native insect herbivory also impacts later life stages of C. vulgare, reducing rosette survival, probability of flowering, and seed production (Louda and Rand 2002, Suwa et al 2010, Suwa and Louda 2012, all of which can reduce population growth rate. For instance, floral herbivory can reduce the population growth rate of C. vulgare by 70% (Tenhumberg et al 2008).…”
Section: Significant Herbivore Impactmentioning
confidence: 99%